Highly Conformal Polymers for Ambulatory Electrophysiological Sensing. Issue 16 (21st April 2022) - Hu, Mingshuang; Zhang, Jun; Liu, Yixuan; Zheng, Xinran; Li, Xiangxiang; Li, Ximing; Yang, Hui
Abstract: Stable ambulatory electrophysiological sensing is widely used for smart e‐healthcare monitoring, clinical diagnosis of cardiovascular diseases, treatment of neurological diseases, and intelligent human–machine interaction. As the favorable signal interaction platform of electrophysiological sensing, the conformal property of on‐skin electrodes is an extremely crucial factor that can affect the stability of long‐term ambulatory electrophysiological sensing. From the perspective of materials, to realize conformal contact between electrodes and skin for stable sensing, highly conformal polymers are in great demand and attracting ever‐growing attention. This review focuses on the recent progress of highly conformal polymers for ambulatory electrophysiological sensing, including their synthetic methods, conformal property, and potential applications. Specifically, three main types of highly conformal polymers for stable long‐term electrophysiological signals monitoring are proposed, including nature silk fibroin based conformal polymers, marine mussels bioinspired conformal polymers, and other conformal polymers such as zwitterionic polymers and polyacrylamides. Furthermore, the future challenges and opportunities in preparing highly conformal polymers for on‐skin electrodes are also highlighted. Abstract : As the signal interaction platform of electrophysiological sensing, the conformal property of on‐skin electrodes is a crucial factor affecting the stability of long‐term ambulatory electrophysiological sensing. This review focuses on the recent progress of highly conformal polymers for ambulatory electrophysiological sensing, including their synthetic methods, conformal property, and applications in the fields of e‐healthcare monitoring, diagnosis of diseases, and intelligent human–machine interaction.